Schooling the Freed People : Teaching, Learning, and the Struggle for Black Freedom, 1861-1876 - Butchart, Ronald E. (Book collections on Project MUSE., 2010)
Butchart combed the archives of all of the freedmen's aid organizations as well as the archives of every southern state to compile a vast database of over 11,600 individuals who taught in southern black schools between 1861 and 1876. He reaches some surprising conclusions: one-third of the teachers were African Americans; black teachers taught longer than white teachers; half of the teachers were southerners; and even the northern teachers were more diverse than previously imagined. His evidence demonstrates that evangelicalism contributed much less than previously believed to white teachers'